1991
DOI: 10.1042/bj2790329
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of sodium pump activity in Xenopus laevis oocytes by expression of heterologous β1 subunits of the sodium pump

Abstract: Recent evidence suggests that the beta subunit of the Na+ pump is essential for the alpha subunit to express catalytic activity and for assembly of the holoenzyme in the plasma membrane. We report here that injection into Xenopus laevis oocytes of cRNAs specific for beta 1 subunit isoforms of the Na+ pump of four species (Torpedo californica, chicken, mouse and rat) causes a time-dependent increase in the number of ouabain-binding sites, both in the plasma membrane and in internal membranes. Expression of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 45 publications
1
63
0
Order By: Relevance
“…However, given that all combinations of Na + /K + ATPase α and β subunits form functional ion pumps (Lemas et al, 1994;Schmalzing et al, 1991;Schmalzing et al, 1997), these results also raise the possibility that neither nrv2 isoform has specific functions and that any β subunit could substitute for Nrv2. We therefore tested whether either of the two other Drosophila Na + /K + ATPase β subunits, nrv1 (Sun and Salvaterra, 1995b) or nrv3 (CG8663), had tube-size or barrier activities.…”
Section: Nrv21 and Nrv22 Both Have Tracheal Tube-size Control And Jmentioning
confidence: 85%
“…However, given that all combinations of Na + /K + ATPase α and β subunits form functional ion pumps (Lemas et al, 1994;Schmalzing et al, 1991;Schmalzing et al, 1997), these results also raise the possibility that neither nrv2 isoform has specific functions and that any β subunit could substitute for Nrv2. We therefore tested whether either of the two other Drosophila Na + /K + ATPase β subunits, nrv1 (Sun and Salvaterra, 1995b) or nrv3 (CG8663), had tube-size or barrier activities.…”
Section: Nrv21 and Nrv22 Both Have Tracheal Tube-size Control And Jmentioning
confidence: 85%
“…(Paul et al, 2003)]. This finding was surprising because in vitro studies concluded that virtually any Na,K-ATPase ␤-subunit can associate with an ␣-subunit to generate a functional ion pump (reviewed by Blanco and Mercer, 1998;Schmalzing et al, 1991). To begin to understand the molecular basis of these Nrv2-specific activities, we created isoform-specific reagents to determine the endogenous subcellular localizations of these proteins (Figs 1, 2 and see Materials and methods).…”
Section: Assays Of Sj Functionmentioning
confidence: 99%
“…Given the high degree of conservation between ␣-subunits in eukaryotes (>70% identity between flies and vertebrates), and the fact that multiple combinations of ␣-and ␤-subunits of the different species can form functional complexes (Schmalzing et al, 1991), we investigated whether a vertebrate ␣-subunit could function in the fly context. We selected rat ␣1 because, of the four vertebrate ␣-subunit isoforms, ␣1 is the only one expressed in all epithelial tissues and therefore seemed the most likely to have a junctional function (Blanco, 2005).…”
Section: Ion-pump-independence Of the Nak-atpase Tube Size And Barrimentioning
confidence: 99%
“…cRNA Synthesis and Oocyte Expression-Capped cRNAs were synthesized from linearized templates with SP6 RNA polymerase (Amersham Pharmacia Biotech) and purified as described (26). For oocyte injection, the cRNAs were dissolved in 5 mM Tris/HCl, pH 7.5, at 0.5 g/l, using the absorbance reading at 260 nm for quantitation (A 1.0 ϭ 40 g/l).…”
Section: Materials and Antibodies-sulfosuccinimidyl-3-(4-hydroxyphenyl)mentioning
confidence: 99%